When the Contract Is Not the Issue, but the Abusive Clauses: Financial Leasing and the Lost Balance - Medina Neyra, Fátima Del Rosario (Revista de Derecho, 2025)
This article examines the regulatory mechanisms aimed at controlling abusive clauses in financial leasing contracts in Peru. The analysis focuses on the role of administrative, judicial, and arbitral authorities, with particular attention to the deficiencies in protecting the lessee, irrespective of their status as a consumer. Using a qualitative methodology, a systematic study is conducted of the main regulatory sources—including Legislative Decree N°. 299, the Civil Code, and the Consumer Protection and Defense Code—along with specialized doctrine and jurisprudential criteria. The diagnosis reveals that the current control system is fragmented, reactive, and ineffective. This fragmentation stems from the coexistence of entities with distinct competencies, such as the Superintendence of Banking, Insurance and Pension Fund Administrators, Indecopi, the Judiciary, and arbitration, which operate without a coordinated approach. Furthermore, its reactive nature means it is primarily activated ex post—that is, after the harm has already occurred. Additionally, its ineffectiveness is evident due to minimal preventive or ex ante control by the SBS, which fails to conclusively mitigate the power imbalance between the parties. Based on this diagnosis, reform proposals are put forward to prevent the use of abusive clauses and improve transparency. The objective is to contribute to a more equitable regulation that balances contractual freedom with the protection of the adhering party.
Keywords: Financial leasing; abusive clauses; mass contracting; civil law; consumer law